Personality Development during Teacher Preparation - Corcoran, Roisin P.; O’Flaherty, Joanne (Frontiers in Psychology, 2016)
Objective: The purpose of this 3-year longitudinal study was to examine pre-service teachers’ personality trajectories as measured by the IPIP Big-Five factor markers during teacher preparation. The relationship between students’ personality traits, social desirability, and prior academic attainment was also examined. Method: This 3-year longitudinal study invited participants from the first year of a 4-year undergraduate (UG) pre-service teacher education program, the class of 2017. The sample consisted of 305 students. Results: The results suggest that extraversion, agreeableness, conscientiousness, emotional stability, and openness to experience were best represented by a non-significant longitudinal change in means. Results also suggest that social desirability predicts agreeableness and emotional stability with small to moderate effect sizes. Conclusion: The study concludes that no value is added to pre-service teachers’ personality traits during 3 years of tertiary education. Furthermore, the data presented does not support the view that academic attainment is a good predictor of personality traits. Implications for educational research, theory, and practice are considered.